Membrane Stabilizing and Preliminary Hypoglycemic Activities of Picrasma javanica (Bangladesh Pharmaceutical Journal, 2013)
The methanol extract of leaves of Picrasma javanica Blume and its n-hexane, carbon tetrachloride, chloroform and aqueous soluble partitionates were evaluated for membrane stabilizing and preliminary hypoglycemic activities. In hypotonic solution and heat-induced conditions, the crude methanol extract inhibited 65.30±0.52% and 36.79±0.38% haemolysis of RBC as compared to 72.79% and 42.12% produced by standard drug, acetyl salicylic acid, respectively (0.10 mg/ml). The crude extract also showed blood sugar lowering efficacy at 200 and 400 mg/ kg body weight, with 48.63% reduction of blood sugar level at 400 mg/kg body weight while the standard drug, Glibenclamide (10 mg/kg body weight) demonstrated 53.7% reduction of blood sugar level at 3rd hour of administration. DOI: http://dx.doi.org/10.3329/bpj.v16i1.14500 Bangladesh Pharmaceutical Journal 16(1): 89-92, 2013